Modeling and Experimental Investigation of Springback in Brass Alloy Sheet Metal V-Bending - Meda, Dekoumwine Parfait (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
One of the most important criteria in a good bending is springback. Springback can be defined as the amount of shape recovered after bending load. Springback value is somehow influenced by some factors like bending force, die opening, bend radius, bend angle, sheet metal thickness and punch holding time, and heat treatment. In this study, springback is investigated in v-bending for yellow brass material (UNS C27000 brass). The investigation of the springback will consider three parameters. The selected parameters to be varying will be the thickness of sheet metal (1.5mm 3mm and 5mm), the die opening (22 and 35mm), and the punch holding time (0 5 and 10 seconds) and all the other parameters will remain constant like the die angle and punch angle (85°). A full factorial multilevel design of experiment (DOE) method is used to conduct the experimental test. Finite element simulation (FEA) using ANSYS IMPLICIT, and experimental investigation results are compared. In addition, machine learning with ANN and SVM methods are used to predict the springback. The analysis of the result done with ANOVA showed interesting facts. The Pareto chart reveals that in comparison with the two other parameters, the sheet thickness has the highest significant effect on the springback and the die opening has the lowest significant effect. In overall the metal behaved approximately like the other metals because the springback decreased when the die opening increased and also when the holding time increased, and also when the sheet thickness increased. However, the brass material went in contradiction with the previous researches on the 3mm sheet thickness. Keywords: springback, finite element analysis (FEA), SVM, ANN, ANOVA.

ÖZ: İyi bir bükülmedeki en önemli kriterlerden biri geri esnektir. Geri yaylanma, yükün bükülmesinden sonra geri kazanılan şekil miktarı olarak tanımlanabilir. Geri yaylanma değeri bir şekilde bükme kuvveti, Kalıp açma, Bükülme yarıçapı, Bükme açısı, sac kalınlığı ve zımba tutma süresi ve Isıl işlem gibi bazı faktörlerden etkilenir. Bu çalışmada sarı pirinç malzeme (UNS C27000 pirinç) için v-bükülmede geri yaylanma araştırılmıştır. Geri esnemenin araştırılması üç parametreyi dikkate alacaktır. Değişecek olan seçilen parametreler sac levha kalınlığı (1.5 3mm ve 5mm), kalıp açıklığı (35 ve 22mm) ve zımba tutma süresi (0 5 ve 10 saniye) ve diğer tüm parametreler sabit kalacaktır. kalıp açısı ve delme açısı (85 °). Deneysel testi yapmak için tam faktöryel çok düzeyli DOE yöntemi kullanılmıştır. ANSYS IMPLICIT kullanılarak sonlu elemanlar simülasyonu (FEA) ve deneysel araştırma sonuçları karşılaştırılmıştır. Ayrıca geri yaylanmayı tahmin etmek için YSA ve SVM yöntemleri ile makine öğrenimi kullanılır. ANOVA ile yapılan sonucun analizi ilginç gerçekler göstermiştir. Pareto şeması, diğer iki parametreye kıyasla, levha kalınlığının geri yaylanma üzerinde en yüksek anlamlı etkiye ve kalıp açıklığının en düşük önemli etkiye sahip olduğunu ortaya koymaktadır. Genel olarak metal yaklaşık olarak diğer metaller gibi davrandı çünkü kalıp açıklığı arttığında ve tutma süresi arttığında ve ayrıca sac kalınlığı arttığında geri esneme azaldı. kalınlık. Anahtar Kelimeler: geri yaylanma, sonlu elemanlar analizi (FEA), SVM, YSA, ANOVA.
Master of Science in Mechanical Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Mechanical Engineering, 2020. Supervisor: Asst. Prof. Dr. Mohammed Bsher A. Asmael.
Keywords: Mechanical Engineering; Metals--Bending; Springback; finite element analysis (FEA); SVM; ANN; ANOVA